The automated accounting system as an organizational and technical component of the accounting policy of PJSC "Firm "Poltavpivo" (Economics and region, 2021)
The article is quite relevant, because in the conditions of continuous changes in the business environment, when companies have to constantly fight for the consumer, while controlling the profitability of their business, because the market economy displaces the weaker, and survive only those companies that most correctly and competently understand the requirements market, so properly organized accounting, skillfully motivated employees to work. The level of business management efficiency increases significantly due to the increasing effectiveness of the accounting process in terms of timeliness of information, its reliability and detail, which necessitates the use of computer software to automate accounting information. In recent years, there has been a trend of general computerization of "digitalization" – over the past three or four years, the number of accounting software has increased significantly. As a result, businesses that carry out economic activities are faced with the task of choosing the appropriate software to automate accounting and management, which will best meet their needs. The novelty of the researched topic is the study of the peculiarities of accounting automation at PJSC "Firm "Poltavpivo" in contrast to the ingrained trend of research of general theoretical aspects of the automated accounting system. Objectives of the study: to determine from the accounting policy of PJSC "Firm "Poltavpivo" which information processing technology (type of software) is used by the company's accounting department; describe the approach of choosing a software product to automate accounting in the enterprise; to analyze the software product as a means to automate the processes of accounting for personnel, labor and wages in the enterprise. The article considers one of the ways of proper organization of accounting in enterprises of various forms of ownership – is the accounting policy. The Decree "On the Accounting Policy" of PJSC "Firm "Poltavpivo" establishes which software product is used by the company's accounting service for automation. The classification characteristic of the existing software for automation of the enterprise accounting system is presented. Areas of application of the ISpro software package are considered. The possibilities of the ISpro software package for labor accounting, accrual and payment of wages are described. The organizational structure of personnel, labor and wage accounting and operations for which the labor and wage accounting subsystem in ISpro is responsible is graphically demonstrated. A number of the main functionalities of personnel and salary accounting in ISpro are revealed. It is proved that accounting automation is an important element of the organizational and technical component of the accounting policy of the enterprise, and its implementation is a complex and time-consuming process, for its success it is necessary to think in advance to solve at least the main problems associated with it.
Keywords: automated accounting system; accounting information; software product; accounting policy; accounting